"Inclusive Growth": A Lacanian Reading. Issue 2 (2nd April 2016) - Basu, Pranab Kanti
Abstract : Until the 1970s, mainstream development theory and the practice of international economic organizations put total faith in a trickle-down approach, refusing to conceive any special policy for those excluded from the gains of modern development. Gradually, both theory and practice are veering toward the mainstream's "inclusive growth." The authors of World of the Third and Global Capitalism conceptualize exclusion and subsequent inclusion as two sides of the same coin that can be theorized through the Lacanian couple of foreclosure/foregrounding. The authors propose a practice of counterhegemony grounded in ethical principles born of the encounter of the working class of the first world and the modes of being and producing of the third world, which are excluded from hegemonic discourse. Many powerful insights are provided by this Lacanian reading of exclusion/inclusion in development theory and practice, but this reading cannot accommodate the role of lived experience and may generate another "end of history."